Pelatihan dan Pendampingan Strategi E-Commerce, Desain dan Label Produk Bagi UMKM di Kecamatan Gunungpati - Hakim , Fitro Nur; Achmad Solechan; Haryo Kusumo; Yuli Fitrianto; Toni Wijanarko AP (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
Problems faced by mosque youth service partners include: Not all MSMEs have good access to stable internet. This can hinder their ability to manage their online store, update inventory, or interact with customers efficiently. Many MSMEs have limitations in terms of human resources, technical expertise and technological infrastructure. This makes it difficult for them to manage the e-commerce platform effectively. Packaging and labels must match the product itself, both in terms of size, shape and other physical characteristics. Finding practical and attractive packaging that also protects the product well can be a challenge. Good packaging design can sometimes involve additional costs, such as graphic designer fees or custom packaging production. For MSMEs with limited budgets, this can be an obstacle. This service activity was carried out in the Gunungpati Village hall on Jalan Magersari Gunungpati, Gunungpati District, Semarang, which included lectures, training and direct mentoring and step-by-step direct assistance. This activity was carried out over 2 days and was attended by 17 participants from MSME actors in the Gunungpati Village area in Gunungpati District, Semarang City and guided by 7 presenters/lecturers from the University of Computer Science and Technology. Training activities along with assistance on product packaging labeling received a good response from partners and participants. Partners, in this case, the Gunungpati Village, appreciates this activity because it can help in developing the MSMEs of its fostered partners in increasing their knowledge and skills regarding labeling. Product labeling will be more perfect if it can be completed with halal legality and a production permit, so education needs to be carried out through training and mentoring regarding this matter, especially for MSMEs in business. Increased understanding of MSME business actors regarding the importance of packaging and label design on products sold, increased quality of product packaging through brands and labels printed on the packaging, and increased income from MSME business actors in Gunungpati Subdistrict.